Carbon Market Clubs and the New Paris Regime - Brewer, Thomas L.; Derwent, Henry; Błachowicz, Andrzej; Grubb, Michael (World Bank, Washington, DC, 2016)
The objective of this paper is to examine the possible relationships between climate clubs and systems and services developed to enable the smooth functioning of Emissions Trading Schemes (ETSs), linked pairs of ETSs and networks of ETSs coming together in various formations that can be described as Carbon Markets Clubs (CMCs). The paper examines the compatibility of CMC systems with different forms of climate clubs or club-like arrangements, and considers how climate clubs using CMC services could contribute to the development of carbon markets internationally and to climate change mitigation. The paper focuses on: (a) how CMC components and infrastructure might assist those climate clubs that have shared emissions reduction or lower-emissions per-unit-of-growth as an overt objective, and (b) club arrangements that include relatively small memberships and or provisions for incentives that affect participation and compliance. This paper is arranged as follows: Section 1 is the Introduction; Section 2 of the paper presents the core concepts and messages of two strands of the club literature that have emerged in climate change studies; In Section 3, the features of climate clubs and club-like arrangements are integrated into a discussion of CMCs initiative, including the potential of linkages among diverse entities; and Section 4 has the conclusions.